Peran Kualitas Pelayanan Penyedia Internet Terhadap Kepuasan Pelanggan - Marluthy, Ayu; Halilah, Ii (Jurnal Riset Bisnis dan Investasi, 2019)
This study aims to determine how much influence the quality of internet provider service to customer satisfaction, using linear regression analysis. The population in this study is the people of Bandung who use or subscribe internet access. Sampling technique used is non-probability sampling by taking samples using quota. The sample of research is 100 respondents. Data collection techniques using observation techniques and questionnaire. The amount of influence service quality to customer satisfaction that is equal to 0,538 or 53,8% change of customer satisfaction can be explained by service quality variable, while the rest equal to 46,2% explained by cause or other factor not examined.